Pendidikan Antikorupsi sebagai Upaya Membangun Generasi Berintegritas - Bintang Auliya Tyananda; Ryan Dwi Prayoga; Tita Ester; Mohammad Fauzil Adhim; Alfira Nur Adella; Nur Hafizah; Dhea Maiza Azzahra; Putri Shandefi; Marisa Zahrani; Eni Lutviana Fadila; Naifa Adelia Nurahmi (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Anti-corruption education is one of the important elements in building the character and integrity of the younger generation. Given the negative impact of corruption that damages the country's social, economic, and political order, this education is an effective preventive means to avoid corrupt practices in the future. This paper aims to explore the concept of anti-corruption education, its role in shaping a generation with integrity, as well as its challenges and implementation strategies. The concept of anti-corruption education involves teaching the values of ethics, honesty, and responsibility that must be instilled from an early age. This education must be applied consistently through formal and non-formal curricula, and involve various parties, including educators, the government, and the community. The challenges faced in the implementation of anti-corruption education include a lack of understanding and awareness of the importance of this education, as well as a culture of corruption that has been internalized in various sectors of life. To overcome these challenges, it is necessary to adopt various implementation strategies, such as the use of technology and social media, as well as collaboration between educational institutions and civil society organizations. Through effective anti-corruption education, it is hoped that a young generation can be created who have integrity, are able to prevent corruption, and contribute to the development of a clean and transparent country.